Upaya Keberatan atas Putusan KPPU ke Pengadilan Niaga: Pembaharuan Berkepastian Hukum - Anjas Putra Pramudito; Nalendra Pradipto; Suseno Suseno; Fairuz Zahirah Zihni Hamdan (Universitas Airlangga, 2023)
AbstractLegal reform has been implemented in the formation of legislation in Indonesia, namely the Copyright Work Law with the omnibus model. Various laws are made into one in the Copyright Act, including the matter of business competition. The new provisions in the Copyright Act that cause controversy are related to the accuracy of the chosen legal domain to be used as a solution in the case of business competition. The shift of authority from the District Court to the Commercial Court to handle the objections to the KPPU ruling raises pros and cons related to the legal certainty resulting from the process of handling the case. Legal research conducted here aims to explain the facts of the applicable law. The results showed that the handling of objections to the decision of KPPU which became the authority of the Commercial Court based on the Copyright Work Law is the right thing. This is because the Commercial Court is a special court of the general judiciary whose judges are more competent in business matters. Besides, this transfer of authority provides legal certainty to the parties to the dispute because the Commercial Court, in this case, is a judicial institution that has the authority to examine, decide, and adjudicate cases following absolute competence and relative competence, and the judge in it acts as judex facti. AbstrakPembaharuan hukum telah dilaksanakan dalam pembentukan peraturan perundang-undangan di Indonesia, yaitu UU Cipta Kerja dengan model Omnibus. Berbagai undang-undang dijadikan satu di dalam UU Cipta Kerja, termasuk perihal perkara persaingan usaha. Ketentuan baru dalam UU Cipta Kerja yang menimbulkan kontroversi adalah terkait ketepatan ranah hukum yang dipilih untuk dijadikan solusi dalam perkara persaingan usaha. Pergeseran kewenangan dari Pengadilan Negeri ke Pengadilan Niaga untuk menangani upaya keberatan atas putusan KPPU menimbulkan pro dan kontra berkaitan dengan kepastian hukum yang dihasilkan dari proses penanganan perkara tersebut. Penelitian hukum yang dilakukan disini bertujuan untuk memberikan penjabaran terkait fakta hukum yang telah berlaku. Hasil penelitian menunjukkan bahwa penanganan upaya keberatan atas putusan KPPU yang menjadi kewenangan Pengadilan Niaga berdasarkan UU Cipta Kerja adalah hal yang tepat. Hal tersebut dikarenakan Pengadilan Niaga merupakan pengadilan khusus dari peradilan umum yang para hakimnya lebih berkompeten dalam perkara perniagaan. Selain itu peralihan kewenangan ini memberikan kepastian hukum kepada para pihak bersengketa karena Pengadilan Niaga dalam hal ini merupakan lembaga peradilan yang memiliki kewenangan memeriksa, memutus, dan mengadili perkara sesuai kompetensi absolut dan kompetensi relatifnya, dan hakim di dalamnya berperan sebagai judex facti.